1983
DOI: 10.1172/jci111108
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with humoral hypercalcemia of malignancy stimulate adenylate cyclase in osteoblastic cells.

Abstract: A B S T R A C T The culture media of three cell lines, a human prostate carcinoma (PC3), a rat Leydig cell tumor (Rice-500), and a rat carcinosarcoma , that were derived from tumors associated with humoral hypercalcemia of malignancy (HHM), were examined for stimulation of adenylate cyclase in ROS 17/2.8 osteoblastic cells and for bone resorptive activity in culture. Cells from a nonhypercalcemic variant of the WRC 256 tumor served as control. Extracts from three solid human tumors, a lung adenocarcinoma from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(93 citation statements)
references
References 17 publications
2
91
0
Order By: Relevance
“…The only conclusion from these observations can be that renal tubular calcium reabsorption plays an important role in the pathophysiology of the humoral hypercalcemia in this model. This conclusion has been strengthened recently by observations that synthetic peptides of PTH-rP increase renal tubular calcium reabsorption in vivo (9), and Leydig tumor cells are known to produce a PTH-rP (35). A different mechanism for increasing renal tubular calcium reabsorption has been proposed by Bijvoet and his colleagues (36).…”
Section: Relative Roles Ofthe Kidney and Bone In Humoral Hypercalcemiamentioning
confidence: 97%
“…The only conclusion from these observations can be that renal tubular calcium reabsorption plays an important role in the pathophysiology of the humoral hypercalcemia in this model. This conclusion has been strengthened recently by observations that synthetic peptides of PTH-rP increase renal tubular calcium reabsorption in vivo (9), and Leydig tumor cells are known to produce a PTH-rP (35). A different mechanism for increasing renal tubular calcium reabsorption has been proposed by Bijvoet and his colleagues (36).…”
Section: Relative Roles Ofthe Kidney and Bone In Humoral Hypercalcemiamentioning
confidence: 97%
“…All of this was strong evidence that HHM cancers produced a substance chemically distinct from PTH, but which acts upon PTH target cells through or in close association with the PTH receptor. Production of such activity was also shown to occur in certain animal tumours associated with humoral hypercalcaemia (Rodan et al, 1983;Rosol et al, 1987), in cell cultures established from these tumours, and in a cell culture established from a renal cortical carcinoma removed originally from a hypercalcaemic patient (Strewler et a1,,1983). …”
Section: Pth-like Activity P R O D U C E D By Cancersmentioning
confidence: 99%
“…By this time appropriately sensitive and high-capacity biological assays for PTH had been developed, and an energetic search for PTH-like activity in tumours resulted in the demonstration that extracts of tumours from HHM patients contained no immunoassayable PTH but were able to activate adenylate cyclase in kidney membranes and increase cyclic AMP production in osteoblast-like cells Rodan et al, 1983). This adenylate cyclase-stimulating activity could be shown only in PTH target tissues, and was inhibited by peptide antagonists of PTH.…”
Section: Pth-like Activity P R O D U C E D By Cancersmentioning
confidence: 99%
“…Both PTH-like activity and TGF activity, especially of alpha class, have attracted much attention as a cause of HHM (Mundy et al, 1985;Rodan et al, 1983;Tashjian et al, 1986), but the simultaneous production of both activities by a particular HHM tumor has rarely been reported. Rat Leydig cell is the representative animal model of HHM and known to produce both PTH-like and TGF-alpha activities (Rodan et al, 1983;Ibbotson el al., 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Rat Leydig cell is the representative animal model of HHM and known to produce both PTH-like and TGF-alpha activities (Rodan et al, 1983;Ibbotson el al., 1983). Employing CAC-8, a serially transplantable tumor line developed from a canine hypercalcemic adenocarcinoma, Rosol et al (1986) reported the simultaneous occurrence of PTH-like activity and EGF-independent TGF activity.…”
Section: Discussionmentioning
confidence: 99%